Faking it! : the performance of forgery in late medieval and early modern culture - Lavender, Philip; Lavender, Philip; Amundsen Bergström, Matilda; Amundsen Bergström, Matilda (Intersections, 2023)
"Faking It! collects eleven chapters which explore the question of forgery from different disciplinary angles: literary historical and art historical contributions share space with discussions of jewels, architecture and coinage. The various case studies take as their focus developments in Renaissance Italy and Early Modern England as well as in France, Germany, Malta, Denmark, Sweden, Iceland, Russia and Australia. While each chapter contributes to a better understanding of the local context of cultural production, together they suggest new answers to how we can understand forgery. The concept of performance allows us to see beyond normative approaches and gain insight into some of the ambiguities concerning the nature of forgery. Contributors include: Brian Boeck, Federica Boldrini, Patricia Pires Boulhosa, Laurent Curelly, Helen Hughes, Jacqueline Hylkema, Philip Lavender, Lorenzo Paoli, Ingrid D. Rowland, Camilla Russo, and Ksenija Tschetschik-Hammerl"--